2004
DOI: 10.1213/01.ane.0000108966.84797.72
|View full text |Cite
|
Sign up to set email alerts
|

Tramadol Added to 1.5% Mepivacaine for Axillary Brachial Plexus Block Improves Postoperative Analgesia Dose-Dependently

Abstract: Tramadol's unique mechanism of action suggests efficacy as a local anesthetic adjunct for peripheral plexus blockade. Our study demonstrates that tramadol, added to mepivacaine for brachial plexus anesthesia, extends the duration and improves the quality of postoperative analgesia in a dose dependent fashion with acceptable side effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
95
1
3

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(106 citation statements)
references
References 18 publications
3
95
1
3
Order By: Relevance
“…Nevertheless, the value of TRAM as an anesthetic adjunct is uncertain; therefore, caution is necessary. 1 Concerning COD in the PNS, it can produce a dose-dependent and reversible decrement in motor function. 9 Our results further support the concept that combinations of different analgesic modalities could reduce the incidence and severity of pain and patient anxiety.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, the value of TRAM as an anesthetic adjunct is uncertain; therefore, caution is necessary. 1 Concerning COD in the PNS, it can produce a dose-dependent and reversible decrement in motor function. 9 Our results further support the concept that combinations of different analgesic modalities could reduce the incidence and severity of pain and patient anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, some adjuvant drugs have been proposed to enhance anesthesia and analgesia, such as clonidine, diazepam, morphine, codeine and tramadol. 1 Although modern LAs are effective and safe for most clinical practice, there are some patients who need more comfort. In these cases, an intense search for antinociceptive agents continues, aiming at improving nerve selectivity, promoting less motor block and lowering systemic toxDeclaration of Interests: The authors certify that they have no commercial or associative interest that represents a conflict of interest in connection with the manuscript.…”
Section: Introductionmentioning
confidence: 99%
“…Robaux et al [15] failed to demonstrate an increase in sensory or motor block when tramadol was added to mepivacaine1.5% for brachial plexus block. But Kapral et al [16] demonstrated that the addition of tramadol 100 mg to mepivacaine 1% for axillary plexus block prolonged sensory and motor block compared with mepivacaine alone or axillary block with tramadol 100 mg i.v.…”
Section: Discussionmentioning
confidence: 97%
“…Previous studies showed conflicting results about the efficacy of tramadol as adjuvant to local anesthetics some studies not prove it is efficiency [13][14][15] and others documented that it has a beneficial effect [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Clonidina, antidepressivos e opioides (Strumper;Duriex, 2004), incluindo o tramadol (Kapral et al, 1999;Robaux et al, 2004) (Collins et al, 1997). Também é uma alternativa aos indivíduos em que a associação analgésica de codeína e acetaminofen não é bem tolerada ou contraindicada (Moore, 1999 (Brau et al, 2000).…”
Section: Ordemunclassified